The Biology of Seeds: Recent Research Advances. Proceedings of the Seventh International Workshop on Seeds, Salamanca, Spain, 2 2003
DOI: 10.1079/9780851996530.0069
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower seed development as related to antioxidant enzyme activities.

Abstract: To determine the effect of changes in detoxifying enzyme activities on seed vigour during seed development and the effects of artificial drying on free-radical scavenging and lipid peroxidation, sunflower (cv. Fructidor) plants were grown in 1999 in France. Flower-heads harvested at 29-55 days after anthesis (DAA) were air-dried at room temperature for at least 7 days until seed moisture content (SMC) reached ∼4.5% FW. Vigour was estimated by the mean time to germination (MTG) of seeds placed at 15 or 20°C in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Interestingly, it has also been demonstrated that desiccation of developing sunflower seeds is associated with an increase in CAT activity thus leading to decreased H 2 O 2 content and lipid peroxidation damage [94,95]. This study has made it possible to identify the catalase gene as being finely regulated at the transcriptional level by the loss of water which is in accordance with the data obtained with cotton [96] and maize [64] seeds.…”
Section: (Re)active Oxygen Species During Seed Development: Acquisitisupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly, it has also been demonstrated that desiccation of developing sunflower seeds is associated with an increase in CAT activity thus leading to decreased H 2 O 2 content and lipid peroxidation damage [94,95]. This study has made it possible to identify the catalase gene as being finely regulated at the transcriptional level by the loss of water which is in accordance with the data obtained with cotton [96] and maize [64] seeds.…”
Section: (Re)active Oxygen Species During Seed Development: Acquisitisupporting
confidence: 78%
“…For example, GR activity increases at the onset of dehydration tolerance in French bean seeds [92] whereas it does not change significantly during desiccation of sunflower seeds [94] and decreases in the case of wheat seeds [83].…”
Section: (Re)active Oxygen Species During Seed Development: Acquisitimentioning
confidence: 99%
“…Response of antioxidant system to water loss depends on dehydration severity and plant species. For example in leaves of grasses the decline of CAT activity in response to drought was observed, but in sunflower and bean embryos the activity of CAT increased during successive dehydration (Bailly et al 2001(Bailly et al , 2003Fu and Huang 2001). Previously, Siminis et al (1994) and de Marco and Roubelakis- Angelakis (1996) reported in tobacco protoplasts that expression of CAT isoenzyme exhibiting relatively low catalytic activity could be related to the induction of totipotency.…”
Section: Discussionmentioning
confidence: 94%
“…Reactive oxygen species (ROS) are known to occur during seed development, where they have a dual function being either cytotoxic or playing a role in development, dormancy breakage, and defence against biotic and abiotic stresses . The activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) and ascorbate peroxidase (APX) significantly changed during seed development . The small heat shock proteins (sHSPs) are usually undetectable in vegetative tissues under normal growth conditions, but can be induced by environmental stresses and developmental stimuli.…”
Section: Introductionmentioning
confidence: 99%